BURNING THE “FLAG of TAWHID”: EX-HTI IDEOLOGY FRAMING In JOURNALISTIC PRODUCTION of MEDIA UMAT (MU) - Saragih, M. Yoserizal (University of Islam Malang, 2024)
This research discusses the journalistic product of the burning of the Tawhid flag produced by Media Ummat (MU) owned by former HTI. Interestingly, the flag burning case was associated with the Prophet's flag, causing various public responses. This research raises questions about how opinion formation and ideological framing are carried out by ex-HTI through journalistic production. Data is collected by tracing the news produced by the publisher Media Umat online which is used as a primary source, while secondary sources are news, journal articles, books and relevant research that discusses the research theme. The data is then analyzed descriptively-analyzed related to the production of news published by Media Umat Online. This study found that views were built using 4 (four) ways, namely religious arguments, through the hands of others, legal narratives, and accusations of an authoritarian government. The ideological framing in question is that the flag that was burned was not an ex-HTI flag but the Prophet's flag. Therefore, Muslims must defend the Islamic propagation. The ideological framing was done to legitimize ex-HTI as defenders of Islam. Other findings show that although ex-HTI has disbanded, the group still exists by fighting against the government.